Pemberdayaan Masyarakat Melalui Inovasi Pembuatan Sabun Padat Bajakah Tampala (Spatholobus littoralis Hassk) pada Masyarakat Kampung Ketupat Samarinda: Community Empowerment Through Innovation in Making Bajakah Tampala Solid Soap (Patholobus littoralis Hassk) in the Community of Ketupat Village, Samarinda - Hamzah, Hasyrul; Luthfi M, Chaerul Fadly Mochtar; Faldi, Faldi; Pradana, Anugrah Riska; Febriani, Riska; Aris, Risna; Mardatilah, Suci; Rani, Frederika Erwina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Bajakah tampala is a plant native to Kalimantan that can be found in forests in the interior of Kalimantan. The use of Bajakah Tampala wood is not widely known by most people. One of the uses of Bajakah Tampala wood is that it can be used as an economically valuable product. This community service takes the form of an empowerment program for PKK and Dasawisma women to provide training in making bajakah solid soap. However, before that, education or outreach was carried out regarding solid soap. Of all participants, 22.2% answered that they knew the process of making solid soap, 44.4% knew about solid soap which has a steel composition, and 20% had an understanding of making solid soap. The results of community service activities showed an increase in the total understanding of participants to 100% answered that they knew the process of making solid soap, 100% answered that they knew about solid soap which has a steel composition, and 100% answered that they understood the process of making solid soap. This activity concludes that all participants can better understand the process of making solid soap products and can feel the benefits of Bajakah solid soap.